1976
DOI: 10.1104/pp.58.6.798
|View full text |Cite
|
Sign up to set email alerts
|

Altered Nitrogenous Pools Induced by the Azolla-Anabaena Azolla Symbiosis

Abstract: The free amino acid and ammonia pools of Azolla caroliniana were analyzed by quantitative column chromatography on columns capable of separating all of the nitrogenous constituents normally found in physiological fluids. Comparisons were made of plants containing symbiotic algae and grown on nitrogen-free media, plants grown on media containing nitrate, and algae-free plants also grown on nitrate media. The major feature of the data was a very high level of intracellular ammonia found in plants which coutain N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Similar results were obtained for A. caroliniana (Newton and Cavins 1976;Peters et al 1985). The levels of ammonia, glutamine, serine, asparagine, alanine, and phenylalanine decreased in the dark, and increased in the light.…”
Section: Diurnalsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were obtained for A. caroliniana (Newton and Cavins 1976;Peters et al 1985). The levels of ammonia, glutamine, serine, asparagine, alanine, and phenylalanine decreased in the dark, and increased in the light.…”
Section: Diurnalsupporting
confidence: 84%
“…Glutamine was much less prevalent in the endophytes from the mature leaves than in the endophytes from the stem apices and in the intact leaf tissues (Fig. 1, Tables 1, 2), On the basis of the excretion of recently fixed :SN2 as ammonia by the heterogenous population of the isolated endophytes (Peters et al 1980) and the high intracellular levels of ammonia found in the association under N2-fixing conditions (Newton and Cavins 1976), it was suggested that filaments fixing N2 actively may not be able to assimilate the fixed N. Naturally, such filaments are highly differentiated and found in mature leaf cavities. Our data support this assumption.…”
Section: Effeet Of Combined Nitrogen In the Mediummentioning
confidence: 97%
“…Current interest in Azolla arises from its symbiotic relationship with a nitrogen-fixing blue-green algae, genus Anabaena. The algae live in leaf cavities of Azolla and are capable of using their own photosynthetic energy to reduce atmospheric nitrogen and produce ammonia which can be used by the fern to meet all its nitrogen requirements (Ashton and Walmsley, 1976;Newton and Cavins, 1976;Marx, 1977). This attribute is of considerable potential importance to agricultural regions with inadequate energy for the production of synthetic nitrogen fertilizers (Marx, 1977).…”
mentioning
confidence: 99%
“…and A. filiculoides Lam. (Peters, 1975Peters, Evans and Toia, 1976;Newton and Cavins, 1976;Ashton and Walmsley, 1976;Newton, 1976;Peters, Toia and Eough, 1977).…”
Section: Introductionmentioning
confidence: 99%